Haptic tele-driving of wheeled mobile robot over the internet via PSPM approach: theory and experiment. (3rd July 2018) - Yang, Hyunsoo; Zuo, Zhiyuan; Lee, Dongjun
Abstract : ABSTRACT: We propose novel haptic tele-driving control frameworks of a wheeled mobile robot (WMR) over the imperfect Internet communication network with varying delay and packet loss. We consider both the dynamic and kinematic WMRs and their various tele-driving modes. By utilizing passive set-position modulation framework, we can guarantee two-port passivity or passivity/stability combination of the closed-loop tele-driving system with some theoretical performance measures. Experiments are performed to show the efficacy of the proposed frameworks using the Internet-emulated communication and a custom-built dynamic/kinematic WMR.